THE EFFICIENCY OF USING EDUCATION VIDEOS ON THE LINEAR PROGRAM MATERIAL AS OBSERVED IN VOCATIONAL HIGH SCHOOL STUDENTS’ MATHEMATICAL COMMUNICATION ABILITY - Laela Zakiah; Asy Syifa Nurul Saomi; Rita Syara; Wahyu Hidayat; Heris Hendriana (Journal Of Educational Experts (JEE), 2018)
This research has a purpose to find out the efficiency of of using education videos to increase the vocational high school students’ mathematical communication ability. The method used for this research was a quasi experiment method where the researcher took two classes as research samples. The first class was the experimental class where the students were shown the education videos and the second class was the control class where the students were taught as usual. The materials which were used for this research was a linear program. The research’s populations were the tenth grade students of SMK AL-Halim Garut with class X Multimedia and X Teknik Komputer dan Jaringan (TKJ) (Class of Computer Techniques and Network)as the samples. From the result of the first normality data analysis test (Pre-test), it was found that the experimental class did not distribute normally, therefore, the research continued by using Mann Whitney’s experiment. Sig.0.456 > 0.05 was resulted from the count, therefore H0 was accepted, it meant that there was no difference between the experimental class and control class. Meanwhile, on the final test (Post-test), the scores of both classes did not distribute normally, therefore Mann Whitney’s experiment was used again to find out. Sig.0.000 > 0.05 was resulted from the count, therefore H0 was rejected. In conclusion, “The efficiency of the students’ mathematical communication ability who got the education videos was more effective than those who were taught as usual on the linear program material”